Road landscape engineering systems of the plain part of Ukraine - Denysyk, H. I.; Ataman, L. V.; Sytnyk, O. I. (Ukrainian Geographical Journal, 2025)
The article examines the issues of functioning, geochemical state, and further development of road landscape engineering systems in the plain part of Ukraine. The study focuses on Podillia, one of the regions with the densest road networks in Ukraine, and the most powerful highway in Ukraine, the Kyiv-Odesa highway. An analysis of studies directly related to the problems of functioning and the impact of road landscape engineering systems on the environment was carried out. Special attention is paid to the methodology of their study: levels of knowledge, approaches, and methods. It is described that, depending on the structural organization, the study of road landscapes should be carried out at three closely interconnected levels: geotechnical, geographical, and landscape science. It is substantiated that among the primary natural and geographical and landscape science approaches to the study of road landscapes are landscape-geodynamic, landscape-geochemical, landscape-ecological, and informational. In studying the RLES, traditional principles and methods were employed, taking into account the features of modern road landscape engineering systems. In studying the natural block, various methods were used, including expeditionary methods, field plots, geophysical and geochemical surveys, semi-stationary methods, literary and cartographic approaches, and others. Geochemical studies were conducted on the current state of soils, snow cover, and, to some extent, plants in the road landscape engineering systems of Podillia and the Kyiv-Odesa highway, with a focus on the presence of heavy metals, including lead, zinc, copper, and iron. Both within the road systems and in the adjacent landscapes, their correlation with maximum permissible concentrations was demonstrated. The prospects for the further development of road landscape engineering systems in connection with modern military and socio-economic processes in Ukraine, as well as the future unification of Ukraine’s road landscapes with those of Western Europe, were considered.
Keywords: Podillia; Kyiv-Odesa highway; road landscape engineering systems; levels of knowledge; geochemical state; development; rational use